Monocyte alteration in elderly hip fracture healing: monocyte promising role in bone regeneration - Clement Shema; Yining Lu; Ling Wang; Yingze Zhang (Immunity & Ageing, 2024)
Abstract Individual aged with various change in cell and cellular microenvironments and the skeletal system undergoes physiological changes that affect the process of bone fracture healing. These changes are accompanied by alterations in regulating critical genes involved in this healing process. Unfortunately, the elderly are particularly susceptible to hip bone fractures, which pose a significant burden associated with higher morbidity and mortality rates. A notable change in older adults is the increased expression of activation, adhesion, and migration markers in circulating monocytes. However, there is a decrease in the expression of co-inhibitory molecules. Recently, research evidence has shown that the migration of specific monocyte subsets to the site of hip fracture plays a crucial role in bone resorption and remodeling, especially concerning age-related factors. In this review, we summarize the current knowledge about uniqueness characteristics of monocytes, and their potential regulation and moderation to enhance the healing process of hip fractures. This breakthrough could significantly contribute to the comprehension of aging process at a fundamental aging mechanism through this initiative would represent a crucial stride for diagnosing and treating age related hip fracture.